Effect of Use of Duckweed Powder as a Fish Feed on Polyculture of Carps (Journal of Environmental Science and Natural Resources, 2015)
An experiment on the use of duckweed (Lemna minor) powder as an ingredient of feed on production of rui (Labeo rohita), mrigal (Cirrhinus cirrhosus) and silver carp (Hypophthalmicthys molitrix) in polyculture, was conducted in six ponds for a period of three months. The experiment was carried out under two treatments, each with three replications. Mean survival rates under treatment-I and treatment-II were 95.55% and 88.88% respectively. The specific growth rate (SGR, % per day) of the fish found under treatment-I and treatment-II were 0.28% and 0.25% respectively. The calculated net fish production of the ponds under treatment-I was 1.416 ton/ha/yr and that of the ponds under treatment-II (control) was 0.846 ton/ha/yr. The net fish production of T-I was significantly (p